Six-year body composition change in male elite senior rugby league players - Jones, B.; Till, K.; Roe, G.; O`Hara, J.; Lees, M.; Barlow, M. J.; Hind, K. (Journal of Sports Sciences, 2018)
This study investigated the change in body composition and bone mineral content (BMC) of senior rugby league (RL) players between 2008 and 2014. Twelve male professional RL players (age, 24.6 ± 4.0 years; stature, 183.4 ± 8.4 cm) received a dual-energy X-ray absorptiometry scan during preseason in 2008 and 2014. Between 2008 and 2014, very likely increases in leg lean mass (LM), total trunk and leg BMC, and a likely increase in arm BMC and possible increases in body mass (BM), total and trunk fat mass (FM), and total, trunk and arm LM were observed. Unlikely decreases and unclear changes in leg and arm FM were also found. Large negative correlations were observed between age and BM (r = -0.72), LM (r = -0.70), FM (r = -0.61) and BMC (r = -0.84) change. Three participants (19.1 ± 1.6 years) increased LM by 7.0-9.3 kg. Younger players had the largest increases in LM during this period, although an older player (30-year old) still increased LM. Differences in body composition change were also observed for participants of the same age, thus contextual factors should be considered. This study demonstrates the individuality of body composition changes in senior professional rugby players, while considering the potential change in young athletes.